Methodology of Improving the Professional Creative Abilities of Future Engineers on the Example of Experimental Training in the Science of Fuels and Lubricants (Eurasian Journal of Learning and Academic Teaching, 2023)
In the article, the application of the demonstration method of experimental training (TMKM) in the educational process creates a foundation for new education, pedagogical solutions to ensure the consistency of education and the inclusion of "Fuel and lubricants" in educational and scientific programs are highlighted.